Industry and collective housing in Magallanes Region: Dynamics and singularities of a mode of territorial occupation, 1885-1971 Industria y hábitat colectivo en la Región de Magallanes: Dinámicas y singularidades de un modo de ocupación territorial, 1885-1971 - Cvitanic Diaz, Boris Alejandro; Matus Carrasco, Daniel Alejandro (My University, 2018)
In the late XIX century the Region of Magallanes experienced an early industrialization process that determined specific forms of occupation of the territory. The challenges imposed by geopolitical issues, and by the scientific interest in the southern geographical area, were followed by a permanent and growing mobilization of labour and economic resources almost exclusively led by private companies and capitals, which occupied the territory according to their particular dynamics and interests. The emergence of livestock production raised the conditions for the creation of a network of dependent and closely related economic activities that were based on the requirements for the development of farming and livestock industries. Therefore, the existence of a frigorific, forestry and mining industry was early favoured, together with the development of an incipient maritime cabotage. This created the necessary conditions for the Region to be incorporated into a system of exchange and production dominated by the European powers. The absence of relevant human settlements and labour, with or without specializations, created ex-nihilo a series of industrial enclaves that acted as nuclei that concentrated the workforce, gave support to the productive activity and constituted an essential vector of a particular occupation mode of the continental and insular geographic Magellanic space. The objective of this research was to establish the singularities detonated by industrialization in the specific field of collective habitat in the Magallanes Region. Consequently, through the notion of industrial enclave, it has been possible to confirm that the development of industry and business strategies in Magallanes determined particular modes of territorial occupation at the southern end of Chile.
Keywords: enclave; industralization; magallanes region